2019
DOI: 10.3389/fmicb.2019.01450
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Iron and Copper on the Oligomerization Dynamics of DR_2577, the Main S-Layer Protein of Deinococcus radiodurans

Abstract: Surface (S)-layers are cryptic structures that coat the external surface of the bacterial cell in many species. The paracrystalline regularity of the S-layer is due to the self-assembling of one or more protein units. The property of self-assembling seems to be mediated by specific topologies of the S-layer proteins as well as the presence of specific ions that provide support in building and stabilizing the bi-dimensional S-layer organization. In the present study, we have investigated the self-assembling mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
3
11
0
Order By: Relevance
“…The SDBC is known to retain metal ions ( 16 ), and in the present report four metal-binding sites were identified and assigned to Cu and Fe ( Fig. 2 ).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The SDBC is known to retain metal ions ( 16 ), and in the present report four metal-binding sites were identified and assigned to Cu and Fe ( Fig. 2 ).…”
Section: Discussionsupporting
confidence: 60%
“…S2 and Table S1 ). The presence of these sites might be important for stabilizing the complex as previously reported ( 16 ).
Figure 2 Metal-binding sites of the SDBC.
…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…3a). According to the p6 symmetry of this S-layer, each T4P-like is surrounded by 6 copies of a smaller complex, the S-layer Deinoxanthin Binding Complex (SDBC), extensively described and characteristic of these cell envelopes (Farci et al , 2016; Farci et al , 2019; Farci et al , 2020; Farci et al , 2021). Recognizable by its triangular shape (with a side length of 90 Å and a thickness of ~30 Å), this ~0.9 MDa complex has the main body embedded in the outer membrane and is located inside of a “cell envelope case” (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These studies identified a dozen proteins involved in the articulated paracrystalline order of the S-layer (Farci et al, 2014) and allocated them into at least two specific hetero-oligomeric complexes, the S-layer deinoxanthin-binding complex (SDBC), accounting for the interpore region of this S-layer (Farci et al, 2016), and a type IV-like piliation system, accounting for the pore region (Farci et al, 2014). Among these complexes, the main one, the SDBC, was broadly characterized both functionally and biochemically (Farci et al, 2015(Farci et al, , 2016(Farci et al, , 2018(Farci et al, , 2019Rothfuss et al, 2006;Ott et al, 2019aOtt et al, , 2019bLim et al, 2019;Adamec et al, 2020), but only recently have some of its structural features been disclosed (Farci et al, 2020).…”
Section: Introductionmentioning
confidence: 99%